2009
DOI: 10.1002/ajmg.a.32660
|View full text |Cite
|
Sign up to set email alerts
|

Occipitoatlantoaxial junction malformation and early onset senile ankylosing vertebral hyperostosis in a girl with MURCS association

Abstract: Recent onset of head mobility limitations associated with significant stiffness along the vertebral column were the predominating symptomatology in a girl with MURCS association. Occipitoatlantoaxial junction malformation complex and vertebral hyperostosis have been identified. Three-dimensional computerized tomography (3-DCT) scan showed assimilation of the anterior arch of the atlas causing basilar invagination. She also had significant thoracic vertebral hyperostosis closely resembling senile ankylosing ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…This case report describes a child with MURCS association who presented from an outside hospital for emergency craniocervical decompression secondary to critical stenosis of the foramen magnum. MURCS association usually does not affect life expectancy [1,2], however there are two reported findings on autopsy of an occipital encephalocele in two fetuses [3]. Foramen magnum stenosis is usually associated to achondroplasia.…”
Section: Discussionmentioning
confidence: 96%
“…This case report describes a child with MURCS association who presented from an outside hospital for emergency craniocervical decompression secondary to critical stenosis of the foramen magnum. MURCS association usually does not affect life expectancy [1,2], however there are two reported findings on autopsy of an occipital encephalocele in two fetuses [3]. Foramen magnum stenosis is usually associated to achondroplasia.…”
Section: Discussionmentioning
confidence: 96%
“…Its incidence is 1 case per 50,000 women [9]. Some MURCS association cases belong to the malformation spectrum of DiGeorge phenotype [10, 11]. Hofstetter et al [12] diagnosed a 16-year-old patient showing the cardinal features of MURCS association accompanied by a persistent left superior vena cava and atrial septal defect, orofacial clefting, and mild reduction deformities of the left hand.…”
Section: Discussionmentioning
confidence: 99%
“…Al Kaissi et al [11] reported a 17-year-old girl with MURCS association and ovarian dysplasia. Tan et al [18] described a patient with bicornuate uterus, right ovarian agenesis, unilateral multicystic dysplastic kidneys, and other birth defects not typically associated with MURCS.…”
Section: Discussionmentioning
confidence: 99%
“…Al Kaissi et al [23] described a 17-year-old girl who presented with MURCS association associated with significant thoracic vertebral hyperostosis closely resembling senile ankylosing vertebral hyperostosis (Forestier disease).…”
Section: Discussionmentioning
confidence: 99%